Investigation of Antioxidant and Anti-inflammatory Properties of Berberine Nanomicelles: In vitro and In vivo Studies - Heidarzadeh, Marjan; Amininasab, Mehriar; Rezayat, Seyed M.; Mousavi, Seyyedeh Elaheh (Current Drug Delivery, 2024)
Introduction: In the present study, neuroprotective effects of berberine (BBR) and berberine nanomicelle (BBR-NM) against lipopolysaccharides (LPS)-induced stress oxidative were investigated, and compared by evaluating their antioxidant and anti-inflammatory activities in PC12 cells, and rat brains. A fast, green, and simple synthesis method was used to prepare BBR-NMs. Method: The prepared BBR-NMs were then characterized using dynamic light scattering (DLS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). In vitro experiments were carried out on the LPS-treated PC12 cell lines to investigate the anti-cytotoxic and antioxidant properties of BBR-NM and BBR. The results showed that BBR-NMs with a diameter of 100 nm had higher protective effects against ROS production and cytotoxicity induced by LPS in PC12 cells in comparison with free BBR. Results: Moreover, in vivo experiments indicated that the activity levels of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), increased in the brain of LPS-treated rats administrated with BBR-NM at the optimum dose of 100 mg.kg-1. BBR-NM administration also resulted in decreased concentration of lipid peroxidation (MDA) and pro-inflammatory cytokines, such as Serum interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α). Conclusion: Overall, BBR-NM demonstrated higher neuroprotective effects than free BBR, making it a promising treatment for improving many diseases caused by oxidative stress and inflammation.
Keywords: SOD